20 µs‐resolved high‐throughput X‐ray photon correlation spectroscopy on a 500k pixel detector enabled by data‐management workflow. (22nd December 2020) - Zhang, Qingteng; Dufresne, Eric M.; Nakaye, Yasukazu; Jemian, Pete R.; Sakumura, Takuto; Sakuma, Yasutaka; Ferrara, Joseph D.; Maj, Piotr; Hassan, Asra; Bahadur, Divya; Ramakrishnan, Subramanian; Khan, Faisal; et al.
Abstract : A high‐throughput data‐management workflow is demonstrated, using a Lambda detector and XSPA‐500k, a novel 52 kHz frame rate 1024 × 512 pixelated detector with no gaps in the read‐out modules. Abstract : The performance of the new 52 kHz frame rate Rigaku XSPA‐500k detector was characterized on beamline 8‐ID‐I at the Advanced Photon Source at Argonne for X‐ray photon correlation spectroscopy (XPCS) applications. Due to the large data flow produced by this detector (0.2 PB of data per 24 h of continuous operation), a workflow system was deployed that uses the Advanced Photon Source data‐management (DM) system and high‐performance software to rapidly reduce area‐detector data to multi‐tau and two‐time correlation functions in near real time, providing human‐in‐the‐loop feedback to experimenters. The utility and performance of the workflow system are demonstrated via its application to a variety of small‐angle XPCS measurements acquired from different detectors in different XPCS measurement modalities. The XSPA‐500k detector, the software and the DM workflow system allow for the efficient acquisition and reduction of up to ∼10 9 area‐detector data frames per day, facilitating the application of XPCS to measuring samples with weak scattering and fast dynamics.